Microscoporogênese, viabilidade e morfologia do grão de pólen em acessos de Cynodon L.C. Rich. (Poaceae) - Silva, Dayanne Medrado (2017)
The Cynodon genus was commonly known as weed for several years, however an increasing interest in studying and using these species has been observed due to their versatile usage, such as for animal forage and also for recovering degraded areas. There are few meiosis studies for Cynodon spp, once the inflorescences are of reduced size, making difficult the standardization of spikelet sampling for observation. The aim of this study was to evaluate the microsporogenesis, pollen grain viability and morphology of four Cynodon accessions. We analyzed two tetraploid accessions of Cynodon dactylon var. dactylon (L.) Pers. (Bermuda grass) and two diploid accessions of Cynodon nlemfuensis var. nlemfuensis Vanderyst (African Bermuda grass) for assessment using classical cytogenetic techniques for meiosis observation and pollen grain viability using both 2% Propionic Carmine and Alexander stain, and acetolysis and scanning electron microscopy to examine the pollen grain morphology. Less than 2% of meiosis abnormalities were observed in the microsporogenesis analysis for all accessions evaluated, nevertheless, the staining tests showed variations for the viability rate between diploid and tetraploid species. C. dactylon var. dactylon pollens showed higher viability rate than the accessions of C. nlemfuensis var. nlemfuensis and both dyes were efficient for this analysis. The assessment of acetolysis and scanning electron microscopy allowed classifying the pollen grains as spheroidal oblates, monoporates and with no ornaments in the exine.